Institutional Aspects of Regional Policy: The Impact of Centralized vs. Decentralized Responsibilities in the Field of Regional Policy on Economic Efficiency and Interregional Cohesion - Martin T. W. Rosenfeld (European Regional Science Association (ERSA), 2003)
Regional policy has – in general – the intention to supporting the efforts of regions with development problems to overcome their current problems and to stimulate an increase in regional economic growth. If the regional policy measures by a jurisdiction are successful, there will be a tendency towards more economic convergence between the various regions within that jurisdiction, with the result of a higher degree of cohesion between these regions, than in a state without regional policy. There are many studies on evaluating the impact of different instruments of regional policy on cohesion. But there are only few investigations so far into the institutional framework of these instruments. One institutional aspect has become more and more relevant in public discussions during the last few years: In federations (e. g. in the EU), there is in general not only one jurisdiction responsible for regional policy, but two, three or even more levels of government; the responsibilities (or: competences) are fragmentated between these levels. The paper presents a theoretical analysis of the impact of the allocation of competences in the field of regional policy on the outcome (interregional cohesion) and on the costs (economic efficiency) of regional policy. The analysis is based on the Theory of Fiscal Federalism, including the Economic Theory of Intergovernmental Grants. All the possible more central or more decentral arrangements of regional policy are located between two polar cases: At one pole, we have an arrangement where only the central level of government (e. g. the EU level) is responsible for regional policy; neither any subcentral unit of government (e. g. at the member state level in the EU), nor the regions which are to be supported (the less developed regions) have any influence for deciding on the implementation of regional policy instruments, and only the central government has to finance regional policy with its own resources. At the other pole, we find an arrangement where only the subcentral units of government and the less developed regions themselves are deciding on regional policy and are responsible for financing. In connection with financing, different categories of grants in aid may be applied. In addition, the arrangements may differ from each other because of different institutions for controlling the activities of the lower levels. The main hypothesis is, that a more decentralized institutional arrangement is not in general more efficient and effective than a more centralized arrangement; but – as compared to the status quo in Europe – a more decentralized arrangement for some public responsibilities would lead to better results in the field of regional policy. Central questions to be answered are: Have subcentral governments (as compared to central units of government) a tendency for neglecting their subregions with development problems' What is the impact of information costs and asymmetrical information on the choice of the level of government for certain (sub-) responsibilities' To which degree is the central influence stimulating – or: paralyzing – the initiative of the regions which are to be supported?
Keywords: 330